2004
DOI: 10.1080/11250003.2004.9525541
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and conservation status ofBombina variegatain Italy (Amphibia, Bombinatoridae)

Abstract: The present paper reports data on distribution, demographic parameters, ecological preferences and conservation status of Bombina variegata variegata and B. v. pachypas from the Italian peninsula. Owing to the wide distribution, we selected as a sam ple the following regions as sample regions: Lombardy, Veneto,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…In suitable habitats along the Apennine chain, B. pachypus was considered as a common species until the mid 1990’s, when population declines and disappearances begun to be reported [38], [39]. Nevertheless, our results date back the presence of the pathogen to at least 1978.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In suitable habitats along the Apennine chain, B. pachypus was considered as a common species until the mid 1990’s, when population declines and disappearances begun to be reported [38], [39]. Nevertheless, our results date back the presence of the pathogen to at least 1978.…”
Section: Discussionmentioning
confidence: 73%
“…Once abundant throughout its range (it was categorized as ‘Least Concern’ in the IUCN Red List of Threatened Species until 2009 [38]), B. pachypus populations have been reported to decline in most parts of its natural range, with the exception of the southernmost portion (the Calabria region), since about the last 15 years [38], [39]. For instance, during a survey carried out in the years 1999–2000 [39], 82% of known sites of presence were confirmed within the Calabria region, whereas 54% were confirmed throughout the rest of the peninsula. Moreover, 64 new sites of presence were discovered in Calabria since 1996, while just 5 new sites were discovered in the other regions [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Italian endemic species has experienced severe population declines in most of its range, with the exception of the southernmost area, over the last 15 yr (Barbieri et al 2004, Andreone et al 2009), and it has been proposed that Bd-related mortality has played a role in this (Stagni et al 2004). Interestingly, we found a delay of at least 1 decade between the first evidence of Bd occurrence and the beginning of the B. pachypus decline.…”
Section: Introductionmentioning
confidence: 59%
“…This species is listed as endangered in the IUCN Red List (as Bombina pachypus; Andreone 2009), and is protected by the Habitats Directive of the European Union (92/43/EEC). Populations in the north and center of the species' range have declined in both number and abundance since the mid-1990s (Barbieri et al 2004). A recent study has found evidence of infection by B. dendrobatidis on specimens across the Italian peninsula (Canestrelli et al 2013).…”
Section: Study Speciesmentioning
confidence: 99%